2011
DOI: 10.1111/j.1472-8206.2011.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus and everolimus intestinal absorption and interaction with calcineurin inhibitors: a differential effect between cyclosporine and tacrolimus

Abstract: The mTOR inhibitors (ImTORs) sirolimus (SRL) and everolimus (EVR) have been increasingly used in renal transplantation as part of calcineurin inhibitor (CNI) sparing or avoidance regimens. Those drugs have low and variable oral bioavailability that is increased when combined with cyclosporine or tacrolimus (TAC). We investigated the mechanisms involved in ImTORs intestinal absorption in vitro and associated it with their drug-drug interactions with CNIs. The transport of ImTORs across Caco-2 cells was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Michaelis–Menten kinetics was incorporated in our model to describe the saturable absorption. This is consistent with a previous study on intestinal absorption, which demonstrated a concentration‐dependent and saturable transepithelial transport of sirolimus across Caco‐2 monolayers 25 . The mechanism of absorption is not very clear, and the model could be further understood once the drug transport mechanisms are elucidated 25 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Michaelis–Menten kinetics was incorporated in our model to describe the saturable absorption. This is consistent with a previous study on intestinal absorption, which demonstrated a concentration‐dependent and saturable transepithelial transport of sirolimus across Caco‐2 monolayers 25 . The mechanism of absorption is not very clear, and the model could be further understood once the drug transport mechanisms are elucidated 25 .…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a previous study on intestinal absorption, which demonstrated a concentration-dependent and saturable transepithelial transport of sirolimus across Caco-2 monolayers. 25 The mechanism of absorption is not very clear, and the model could be further understood once the drug transport mechanisms are elucidated. 25 Cummins et al 26 studied the cellular pharmacokinetics of sirolimus in CYP3A4-transfected Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Conversely, P-gp up-regulation appears to protect proximal renal tubular cells from cadmium-induced apoptosis. 55 Although mTOR inhibitors are well known to act simultaneously like CNIs as substrates, and as inhibitors for P-gp, 46,52,56,57 similar associations between P-gp expression and everolimus nephrotoxicity have not been reported so far.…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
“…No correlation has been observed between sirolimus blood concentrations and bodyweight, gender, age, or dose [16]. Intestinal CYP3A metabolism and intestinal P-gp counter-transport, intestinal membrane permeability, and hepatic first-pass all affect bioavailability and probably also influence sirolimus absorption because the drug is a substrate for these enzymes and transporters [17] (Fig. 2) …”
Section: Pharmacokinetics Absorptionmentioning
confidence: 97%